Anthropometric, Morphometric and Posture Evaluation of The Tallest Living Person In The World: A Case Report - Erhan Kara (Selcuk University, 2020)
This study aims to identify the anthropometric and morphometric characteristics and reveal the postural disorder of the male case called S.K who was diagnosed with Gigantism (pituitary gigantism) caused by hypersecretion of pituitary tumor related growth hormone and entitled as the tallest person alive in the world with a height of 2.51 cm in the Guinness World Records in 2009. Height, weight, body mass index, upper extremity lengths, lower extremity lengths, skinfold thickness, upper and lower extremity diameters, upper and lower extremity perimeters, chest depth and hand grip strength were measured for anthropometric measurement. 8 different body segments were calculated and analyzed using The Posture Screen Mobile® application for posture evaluation. Disorders in these segments were identified based on forward tilt of head (Anterior/Lateral -AL), position of head (A-L), tilt and position of shoulder (A-L), position of ribcage (left-right), position of pelvis (left-right), pelvic tilt (left-right) and load on head (lb. and kg) (Figure 1.). The measurements revealed that the case surprisingly had anthropometric and morphometric values above normal human dimensions and that, there was also no other living human being with numerically the same values. (Table 2-8). As a result, since the fact investigated has an extreme length due to jigantism, he has taken his place in the Guinness Book of records as the world's longest living person with a long length.